Pengaruh Electronic Word Of Mouth dan Brand Image Terhadap Keputusan Pembelian Secondate Beauty - Valentina, Natasha; Erdiansyah, Rezi (Prologia, 2021)
This study aims to determine the effect of electronic word of mouth and brand image on purchasing decisions of Secondate Beauty. The theories discussed in this study are communication theory, electronic word of mouth, brand image, and purchase decisions. This research uses a quantitative approach with a survey method. The population of this research is the people of Jakarta who have bought Secondate Beauty products. The sampling technique used was non-probability with a purposive sampling approach, with 140 respondents. The technique of collecting data using a questionnaire. Test the validity of the data using the validity, reliability, and normality test. And to test data processing and analysis using multiple linear regression test, T test, F test, correlation coefficient and coefficient of determination. All of these tests were processed by researchers using IBM SPSS 25 software. This program was used to determine the extent of the influence of electronic word of mouth and brand image on the purchasing decision of Secondate Beauty. The results of this study indicate that Ha is accepted, which means that this means that electronic word of mouth and brand image have a significant effect on purchasing decisions from Secondate Beauty products. Penelitian ini bertujuan untuk mengetahui pengaruh electronic word of mouth dan brand image terhadap keputusan pembelian Secondate Beauty. Teori yang dibahas di penelitian ini adalah teori komunikasi, electronic word of mouth, brand image, dan keputusan pembelian. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survey. Populasi dari penelitian ini adalah masyarakat Jakarta yang pernah membeli produk Secondate Beauty. Teknik penarikan sampel yang digunakan adalan non-probability dengan pendekatan purposive sampling, responden yang berjumlah 140 orang. Teknik pengumpulan data dengan menggunakan kuesioner. Uji keabsahan data menggunakan uji validitas, reliabilitas, dan normalitas. Dan untuk uji pengolahan dan analisis data menggunakan uji regresi linear berganda, uji T, uji F, koefisen korelasi dan koefisien determinasi. Semua uji ini diolah peneliti dengan menggunakan software IBM SPSS 25. Program ini digunakan untuk mengetahui sejauh mana pengaruh electronic word of mouth dan brand image terhadap keputusan pembelian Secondate Beauty. Hasil dari penelitian ini mengindikasikan Ha diterima, yang berarti ini menunjukkan bahwa electronic word of mouth dan brand image berpengaruh secara signifikan terhadap keputusan pembelian dari produk Secondate Beauty.